(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Ostium secundum atrial septal defect (OS-ASD) is one of the most common congenital heart diseases and is associated with chronic left-to-right shunting, resulting in right atrial and right ventricular volume overload. Transcatheter device closure has become the preferred treatment modality for suitable defects due to its safety, efficacy, and favorable outcomes. This study aimed to evaluate changes in right heart dimensions and function following transcatheter device closure of OS-ASD using serial echocardiographic assessment. Methods: This prospective observational study was conducted in the Department of Paediatrics at Sree Mookambika Institute of Medical Sciences, Kulasekharam, Tamil Nadu, from September 2025 to March 2026. Thirty consecutive patients aged more than 12 years with ostium secundum atrial septal defects undergoing transcatheter device closure were enrolled. Clinical evaluation and transthoracic echocardiography were performed before the procedure and during follow-up at 1 week, 1 month, 3 months, and 6 months. Echocardiographic parameters assessed included right atrial size, right ventricular dimensions, tricuspid annular plane systolic excursion (TAPSE), myocardial performance index (MPI), and right ventricular systolic pressure (RVSP). Statistical analysis was performed using repeated-measures ANOVA, with a p-value <0.05 considered statistically significant. Results: Following device closure, there was a significant reduction in right atrial and right ventricular dimensions, indicating progressive reverse remodeling of the right heart. Right ventricular systolic pressure also showed a significant decline during follow-up. Functional assessment demonstrated significant improvement in TAPSE and myocardial performance index, reflecting enhanced right ventricular systolic performance. These improvements were evident as early as the first follow-up visit and were sustained throughout the 6-month follow-up period. Conclusion: Transcatheter device closure of ostium secundum atrial septal defect results in significant improvement in right heart dimensions and right ventricular function, with favorable echocardiographic remodeling observed over six months. The findings support the effectiveness and safety of device closure as a minimally invasive treatment option for appropriately selected patients with OS-ASD.